A Study on Quality of Service at Skill Vertex, Bangalore - S. Sasirekha, Deepika T, Arshan M, Karthikeyan B, Mohanraj R (Mathematical Statistician and Engineering Applications, 2021)
This project titled “A Study On Quality of service Of Skill Vertex “.The main objectiveof this study is to determine the quality of service that is by the Skill Vertex to its customers. Primary, well defined objectives are framed to the study then questionnaire is preparedbased on defined objectives. The prepared questionnaire is used to get the direct response from theselected sample size of 120 customers of Skill Vertex on the basis of convenience sampling method.The response given by the employees are analyzed and interpreted using different statistical tools such as chi square test and correlation methods.From this analysis some general findings arrived and that are more related with the framed objectives for this study. It is found that the overall quality of service score is within the acceptable level. According to the findings, the suggestions and recommendations are given whichwill be more helpful for the organization.